2015
DOI: 10.1093/scan/nsv059
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation ability varies in relation to intrinsic functional brain architecture

Abstract: This study investigated the neural basis of individual variation in emotion regulation, specifically the ability to reappraise negative stimuli so as to down-regulate negative affect. Brain functions in young adults were measured with functional Magnetic Resonance Imaging during three conditions: (i) attending to neutral pictures; (ii) attending to negative pictures and (iii) reappraising negative pictures. Resting-state functional connectivity was measured with amygdala and dorsolateral prefrontal cortical (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
89
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 43 publications
4
89
2
Order By: Relevance
“…This finding is consistent with results from other neuroimaging studies suggesting a right amygdala specific role in emotion regulation in healthy subjects (Uchida et al, 2015) . In bipolar disorder, a previous study comparing task related connectivity in bipolar mixed or manic states to the depressed state demonstrated changes in amygdala connectivity selectively in the right amygdala (Cerullo et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with results from other neuroimaging studies suggesting a right amygdala specific role in emotion regulation in healthy subjects (Uchida et al, 2015) . In bipolar disorder, a previous study comparing task related connectivity in bipolar mixed or manic states to the depressed state demonstrated changes in amygdala connectivity selectively in the right amygdala (Cerullo et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…cortical activation in response to pictures with a negative emotional valence compared to neutral pictures (e.g. figure 2 from (Uchida et al, 2015)). Testing this hypothesis may be accomplished by follow-on studies that examine how FC in this network predicts responses to emotionally valenced stimuli in subjects with bipolar disorder and HC subjects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have linked reappraisal with increased activity in the dorsolateral and ventromedial prefrontal cortices (Buhle et al, 2013;Goldin, McRae, Ramel, & Gross, 2008), and both reappraisal and suppression have been associated with decreased activity in the amygdala (Buhle et al, 2013;Chen, Chen, Yang, & Yuan, 2017). Decreased coupling between the amygdala and medial prefrontal cortex has been associated with reappraisal, whereas increased coupling between the amygdala and dorsal anterior cingulate cortex has been associated with suppression (Pan et al, 2018;PicĂł-PĂ©rez et al, 2018;Uchida et al, 2015). Decreased coupling between the amygdala and medial prefrontal cortex has been associated with reappraisal, whereas increased coupling between the amygdala and dorsal anterior cingulate cortex has been associated with suppression (Pan et al, 2018;PicĂł-PĂ©rez et al, 2018;Uchida et al, 2015).…”
mentioning
confidence: 99%
“…Similarly, research has identified how patterns of intrinsic functional connectivity differ between suppression and reappraisal. Decreased coupling between the amygdala and medial prefrontal cortex has been associated with reappraisal, whereas increased coupling between the amygdala and dorsal anterior cingulate cortex has been associated with suppression (Pan et al, 2018;PicĂł-PĂ©rez et al, 2018;Uchida et al, 2015).…”
mentioning
confidence: 99%